Investment Opportunity Set (IOS) Sebagai Pemoderasi Pengaruh Profitabilitas dan Kepemilikan Manajerial Terhadap Kebijakan Utang - Rahayu, AA Putri; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi, 2018)
This study aims to determine the effect of profitability and managerial ownership of debt policy in moderation by Investment Opportunity Set (IOS). This research was conducted at a manufacturing company listed on Indonesia Stock Exchange (IDX) period 2012-2014. The number of sample is 126 companies, with purposive sampling method. Data analysis technique used is Moderated Regression Analysis (MRA).Based on the results of the analysis found that profitability does not negatively affect debt policy. Managerial ownership negatively affects debt policy. Investment opportunity set (IOS) is unable to reinforce the negative effect of profitability on debt policy. Investment opportunity set (IOS) weakens the negative influence of managerial ownership on debt policy. Keywords : Debt policy, profitability, managerial ownership, and investment opportunity set (IOS).